Penentuan Nilai Pemungutan Pajak Bea Perolehan Peralihan Tanah oleh Pemerintah dalam Penyelenggaraan Otonomi Daerah - I Gde Chandra Astawa Widhiasa; I Wayan Arthanaya; Luh Putu Suryani (Jurnal Preferensi Hukum, 2020)
One of the authorities possessed by the regional government is in terms of tax collection, one of which is the Land Title Acquisition Fees (BPHTB) carried out by the Regional Revenue Agency. The legal basis is Law Number 28 of 2009. The proceeds of the revenue which constitute state revenue are handed over to the regional government to finance development in the regions and realize regional autonomy. This study aims to identify and describe the basis for local government regulations to determine the value of an object of land rights as a tax object and to regulate the authority to collect BPHTB in relation to local regulations. Researchers used an empirical method, namely an approach with legal aspects from the results of research in the field through data collected through interviews and observations. The results of research which are based on BPHTB which are the final results of BPHTB are the results of the Acquisition of Tax Objects (NPOP). NPOP is stipulated in Article 87 of Law No.28 of 2009 concerning Regional Taxes and Regional Levies. Fees for acquisition of land rights that were not previously imposed in the case of transfer, with the issuance of Law Number 21 of 1997 which was later bound by Law Number 21 of 2000 which gave regional government authority to impose it.